Transport equations for low density soliton gas - Baryakhtar, I.V.; Baryakhtar, V.G. (Вопросы атомной науки и техники, 2001)
We present the theory of transport phenomena in a gas of solitons for Sinus Gordon model system. The general case of relaxation phenomena is considered. A special attention is paid for a small density non-relativistic gas of breathers. Such kinetic coefficients as diffusion, thermal conductivity, and internal friction are found. It is shown, that diffusion coefficient and internal friction coefficient equal each other.